Top-down laminar organization of the excitatory network in motor cortex - Weiler, Nicholas (2008)
Cortical layering is a hallmark of the mammalian neocortex and a major determinant of local synaptic circuit organization in sensory systems. In motor cortex, the laminar organization of cortical circuits has not been resolved, yet their input-output operations are crucial for motor control. Here, we developed a general approach for estimating layer-specific connectivity in cortical circuits, and applied it to mouse motor cortex. From these data we computed a laminar presynaptic→postsynaptic connectivity matrix, W(post,pre), revealing a complement of stereotypic pathways dominated by layer 2 outflow to deeper layers. Network modeling predicted, and experiments with disinhibited slices confirmed, that stimuli targeting upper but not lower cortical layers effectively evoked network-wide events. Thus, in motor cortex, descending excitation from a preamplifier-like network of upper-layer neurons drives output neurons in lower layers. Our analysis provides a quantitative wiring diagram framework for further investigation of the excitatory networks mediating cortical mechanisms of motor control.